2000
DOI: 10.1016/s1097-2765(00)00058-7
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint-Dependent Activation of Mutagenic Repair in Saccharomyces cerevisiae pol3-01 Mutants

Abstract: The Saccharomyces cerevisiae DNA polymerase delta proofreading exonuclease-defective mutation pol3-01 is known to cause high rates of accumulating mutations. The pol3-01 mutant was found to have abnormal cell cycle progression due to activation of the S phase checkpoint. Inactivation of the S phase checkpoint suppressed both the pol3-01 cell cycle progression defect and mutator phenotype, indicating that the pol3-01 mutator phenotype was dependent on the S phase damage checkpoint pathway. Epistasis analysis su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
74
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 65 publications
7
74
0
Order By: Relevance
“…5 could be triggered by mutations other than pol3-R696W, and whether it can operate in human cells. In yeast, the requirement of Dun1 for the mutator effect has been observed previously for two other Polδ variants (33,73). These findings suggest that high sensitivity of replicative DNA polymerase mutants to fluctuation of intracellular dNTP levels could be a general phenomenon.…”
Section: Discussionsupporting
confidence: 75%
“…5 could be triggered by mutations other than pol3-R696W, and whether it can operate in human cells. In yeast, the requirement of Dun1 for the mutator effect has been observed previously for two other Polδ variants (33,73). These findings suggest that high sensitivity of replicative DNA polymerase mutants to fluctuation of intracellular dNTP levels could be a general phenomenon.…”
Section: Discussionsupporting
confidence: 75%
“…The pol2-4 and pol2-M644G alleles increase mutation rates threefold and 10-fold, respectively ( Fig. 2A (5,19,21,45). Mutation rates of pol2-4 dun1Δ cells were not statistically different from mutation rates of WT or dun1Δ cells, whereas pol2-M644G dun1Δ cells failed to form visible colonies upon shuffling ( Fig.…”
Section: Dun1 Is Required For the Mutator Phenotype Or Viability Of Pol2mentioning
confidence: 92%
“…Previous studies observed that the mutator phenotype of proofreading-deficient Pol δ (encoded by the pol3-01 allele) partially depends on the Dun1 effector kinase (20,21) (Fig. 1), which lies directly downstream of the mitosis entry checkpoint 1 (Mec1) [mammalian ataxia telangiectasia and Rad3-related protein (ATR)] and Rad53 [mammalian checkpoint kinase (Chk)1] kinases in the S-phase checkpoint pathway (22,23) (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Defects in Pol e or Pol d proofreading increase the spontaneous mutation rate in a manner consistent with major roles for these polymerases in leadingand lagging-strand synthesis (Morrison et al 1991;Simon et al 1991;Morrison and Sugino 1994;Shcherbakova et al 1996;Tran et al 1999;Karthikeyan et al 2000;Greene and Jinks-Robertson 2001). Interestingly, the Pol d proofreading defect generates a mutator phenotype 5-to 30-fold greater than that observed in Pol e proofreading-deficient strains (Morrison and Sugino 1994;Shcherbakova et al 1996;Tran et al 1999;Datta et al 2000;Karthikeyan et al 2000;Greene and Jinks-Robertson 2001;Pavlov et al 2004), and the spectra of spontaneous mutations that arise in Pol e and Pol d proofreading-deficient strains differ, which may reflect distinct error specificities of the polymerases as well as strand-specific effects (Morrison and Sugino 1994;Karthikeyan et al 2000;Pavlov et al 2002Pavlov et al , 2003Shcherbakova et al 2003;Fortune et al 2005). Mouse cells with defects in Pol e or Pol d proofreading also exhibit increased mutation rates (Goldsby et al 2002;Albertson et al 2009), and, consistent with distinct roles in DNA replication, the types of tumors that develop in Pol e and Pol d proofreading-deficient mice differ markedly (Albertson et al 2009).…”
mentioning
confidence: 99%